The Law of Emerging Adults - Clare Ryan (Washington University Law Review, 2020)
Law tends to divide people into two groups based on age: children and adults. The age of majority provides a bright line between two quite different legal regimes. Minority is characterized by dependency, parental control, incapacity, and diminished responsibility. Adulthood is characterized by autonomy, capacity, and financial and legal responsibility. Over the course of the twentieth century, evolving understandings of adolescence in law and culture produced a staged process of increasing liberty and responsibility up to the age of majority. After eighteen, however, the presumption of adulthood remains strong. Today, a combination of psychological and social factors has extended the process of becoming an adult well into legal adulthood. Psychologists call this life phase “emerging adulthood” and have identified it as a crucial period of transition and exploration. This Article argues that emerging adults should be treated as a distinct legal category. This life stage differs both from childhood and adulthood with regard to three key relationships: the parent-child; the individual and the market; and the individual and the state. Laws are beginning to treat emerging adults differently. This Article examines the developing law of emerging adults, by focusing on parental support obligations, federal interventions, and punishment. Looking to the future, this Article then provides a framework for further legal reform that is guided by three principles, which reflect emerging adulthood’s unique economic vulnerability, developing autonomy, and capacity to learn from mistakes. I argue that a broad array of legal tools could provide individuals with greater autonomy than exists during minority, but greater protection than adulthood typically provides. Such tools include staging responsibilities and entitlements over time, requiring licensing or consultation, or extending state and parental obligations toward emerging adults.
Keywords: Emerging adults; Young adults; Parental support; Entitlement programs; Criminal law; Age of majority; Autonomy; Economic vulnerability